EFEKTIVITAS BANTUAN UMKM DAN STRATEGI PENGUATAN UMKM DI KOTA MAGELANG - Hutajulu, Dinar Melani; Islami, Fitrah Sari (Center for Economic Studies Universitas Katolik Parahyangan, 2024)
The condition of SMEs during the COVID-19 pandemic requires support from the government. So that the government provides assistance to keep MSMEs afloat. The research aims to determine the effectiveness of government assistance to MSMEs and determine the appropriate strengthening strategy. The research was conducted in Magelang City with the object of research, namely the recipients of BPUM assistance in 2021 as many as 32 respondents. The method of data collection was carried out by observation, interviews, and filling out questionnaires. The analysis in this study includes descriptive analysis, one sample chi-square test analysis, Wilcoxon-signed rank test analysis, and SWOT analysis. The results show different opportunities for each micro-enterprise in obtaining BPUM assistance based on the length of business, type of business, and type of product. Another finding is that BPUM assistance is effective in increasing micro-enterprises in terms of capital, production and added value. However, it is not effective in increasing the workforce. Strategies such as unique products, good relations with partners, mastery of digital marketing, promotion, improving the quality of human resources, innovation and utilization of tourism potential are the right strategies to implement.